THE LANGUAGE FEATURES OF MALE AND FEMALE BEAUTY INFLUENCERS IN YOUTUBE VIDEOS - Clara Herlina Karjo; Stephani Wijaya (University of Kuningan, 2020)
Nowadays, the beauty community has a rapid growth of beauty influencers from both genders. The language style that is used on each gender has its own features and characteristics that can be explored from video sharing platform, YouTube. The aim of this study is to find the language features and distinctive characteristics of the male and female beauty influencers and the differences of comments from their audience. The writer applies qualitative research method by using text analysis of the video script. The data shows that male and female beauty influencers have shown differences in their features and characteristic of language. Men beauty influencers tend to be more straightforward and directive. They also use a more plain and simple words. On the other hand, the women beauty influencers are more polite and intimate in using language. This study is hoped to be the foundation for further research in the same topic of language feature in gendered community within limited topic especially in this modern era.